Dilemmas for the pathologist in the oncologic assessment of pancreatoduodenectomy specimens: An overview of different grossing approaches and the relevance of the histopathological characteristics in the oncologic assessment of pancreatoduodenectomy specimens - Soer, Eline; Brosens, Lodewijk; van de Vijver, Marc; Dijk, Frederike; van Velthuysen, Marie-Louise; Farina-Sarasqueta, Arantza; Morreau, Hans; Offerhaus, Johan; Koens, Lianne; Verheij, Joanne (Virchows Archiv : an international journal of pathology, 2018)
A pancreatoduodenectomy specimen is complex, and there is much debate on how it is best approached by the pathologist. In this review, we provide an overview of topics relevant for current clinical practice in terms of gross dissection, and macro- and microscopic assessment of the pancreatoduodenectomy specimen with a suspicion of suspected pancreatic cancer. Tumor origin, tumor size, degree of differentiation, lymph node status, and resection margin status are universally accepted as prognostic for survival. However, different guidelines diverge on important issues, such as the diagnostic criteria for evaluating the completeness of resection. The macroscopic assessment of the site of origin in periampullary tumors and cystic lesions is influenced by the grossing method. Bi-sectioning of the head of the pancreas may offer an advantage in this respect, as this method allows for optimal visualization of the periampullary area. However, a head-to-head comparison of the assessment of clinically relevant parameters, using axial slicing versus bi-sectioning, is not available yet and the gold standard to compare both techniques prospectively might be subject of debate. Further studies are required to validate the various dissection protocols used for pancreatoduodenectomy specimens and their specific value in the assessment of pathological parameters relevant for prognosis.